Electron dynamics of interatomic Coulombic decay in quantum dots induced by a laser field - Bande, Annika (The journal of chemical physics, 2013)
In this paper we investigated the dynamics of an electron in the presence of a time-dependent laser field in a model potential for a two-level single-electron semiconductor quantum dot (QD) that is capable of undergoing interatomic Coulombic decay (ICD) together with an electron bound to a neighboring QD. We demonstrate that ICD can be initiated by coupling the two-level QD to either a continuous or a pulsed moderate to strong laser and we obtain the total and partial decay widths of the resonance excited state in agreement with that from the solely decay of the resonance [A. Bande, K. Gokhberg, and L. S. Cederbaum, J. Chem. Phys. 135, 144112 (2011) https://doi.org/10.1063/1.3646205.]. A detailed discussion of the effects of direct ionization by the laser in single- or multi-photon process as well as Rabi oscillations is furthermore presented.